De novo-synthesized ceramide is involved in cannabinoid-induced apoptosis. - Gómez del Pulgar, Teresa (2002)
Delta(9)-Tetrahydrocannabinol (THC) and other cannabinoids have been shown to induce apoptosis of glioma cells via ceramide generation. In the present study, we investigated the metabolic origin of the ceramide responsible for this cannabinoid-induced apoptosis by using two subclones of C6 glioma cells: C6.9, which is sensitive to THC-induced apoptosis; and C6.4, which is resistant to THC-induced apoptosis. Pharmacological inhibition of ceramide synthesis de novo, but not of neutral and acid sphingomyelinases, prevented THC-induced apoptosis in C6.9 cells. The activity of serine palmitoyltransferase (SPT), which catalyses the rate-limiting step of ceramide synthesis de novo, was remarkably enhanced by THC in C6.9 cells, but not in C6.4 cells. However, no major changes in SPT mRNA and protein levels were evident. Changes in SPT activity paralleled changes in ceramide levels. Pharmacological inhibition of ceramide synthesis de novo also prevented the stimulation of extracellular-signal-regulated kinase and the inhibition of protein kinase B triggered by cannabinoids. These findings show that de novo-synthesized ceramide is involved in cannabinoid-induced apoptosis of glioma cells.